EFFECTS OF ETORICOXIB, ZILEUTON, AND THEIR COMBINATION ON URINARY PGE-M AND LTE4 LEVELS IN IRAQI SMOKERS: A COMPARATIVE STUDY - from publication on author’s request, This article has been retracted (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
THIS ARTICLE HAS BEEN RETRACTED FROM PUBLICATION ON AUTHOR’S REQUEST